On Hyponormality of Toeplitz Operators on the Weighted Bergman Space - Hazarika, Munmun; Phukon, Ambeswar (Communications in Mathematics and Applications, 2012)
In this paper we give necessary and sufficient conditions for the hyponormality of the Toeplitz operator T_φ on the weighted Bergman space A^2_α(D) for φ(z)=a_-3z^3+a_-1z+a_1z+a_3z^3 and φ(z)=a_-3z^3+a_-2z^2+a_2z^2+a_3z^3.